The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jsfa.9464
|View full text |Cite
|
Sign up to set email alerts
|

Designing and evaluation of urea microcapsules in vitro to improve nitrogen slow release availability in rumen

Abstract: BACKGROUND: There is a growing interest in the development of novel and innovative vehicles for controlled release of urea into the rumen, aiming to provide ammonia-N for the biosynthesis of proteins of bacterial origin and to prevent urea intoxication by direct feeding to livestock. Urea microencapsulation is a system that can control the release of urea to be slow and steady. RESULTS:The amount of encapsulated urea was 69% of CSU (calcium silicate + urea + Eudragit RS100 ® + dichloromethane) and 71% of ACU (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…In this study, the similarity in both in vitro degradability of IVDMD and IVOMD at 12 h after incubation could be attributed to the deceleration and increased stability of the core substrate facilitated by the microencapsulated wall of MiEn-LEDRAGON in the in vitro degradation process 53 , 54 . This effect may lead to a temporary slowdown in the efficiency of microbial decomposition, resulting in similar outcomes for a short period 55 .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this study, the similarity in both in vitro degradability of IVDMD and IVOMD at 12 h after incubation could be attributed to the deceleration and increased stability of the core substrate facilitated by the microencapsulated wall of MiEn-LEDRAGON in the in vitro degradation process 53 , 54 . This effect may lead to a temporary slowdown in the efficiency of microbial decomposition, resulting in similar outcomes for a short period 55 .…”
Section: Discussionmentioning
confidence: 69%
“…The breakdown of the insoluble fraction occurred at a rate approximately four times slower than the breakdown of the soluble fraction during anaerobic digestion 52 . This leads to a decline in the microbial degradation efficiency in the rumen, causing a gradual reduction or slowdown in the degradation process, which is to achieve higher and longer stability of the core substrate within the ruminal inoculum 53 , 54 . Similarly, Ibrahim and Hassen 55 demonstrated that the slow release provided by microencapsulated tannin effectively protects the bioactive compound, leading to a slow degradation rate until it reaches the target site.…”
Section: Discussionmentioning
confidence: 99%
“…In order to circumvent these problems and obtain better efficiency in the nitrogen use by ruminal microorganisms, different types of slow-release urea (SRU) such as biuret, starea (extruded urea), urea phosphate, oil-based coatings, urea treated with formaldehyde, and urea coated with polymer were developed 3 . These products decrease the chances of intoxication and can improve bacterial growth, as they are able to maintain a constant availability of nitrogen in the rumen fluid 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as the most important nonprotein nitrogen source in ruminants, urea has a vital function in supplementing the protein of ruminants. By preparation sustained-release urea microcapsules based on oil and polymer, the ammonia produced by urea in the rumen is prevented from exceeding the rate of microbial utilization(Cherdthong & Wanapat, 2010;Galo, Emanuele, Sniffen, White, & Knapp, 2003;Lira-Casas et al, 2019;Ma, Wang, Hahn, & Sanchez, 2016;Pinos-Rodriguez, Peña-Avelino, González-Muñoz, Bárcena-Gama, & Salem, 2010;).…”
mentioning
confidence: 99%